Theabrownin ameliorates liver inflammation, oxidative stress, and fibrosis in MCD diet-fed C57BL/6J mice - Zhen, Qingcai; Liang, Qijian; Wang, Hongchun; Zheng, Yan; Lu, Zhongting; Bian, Chunyong; Zhao, Xiulan; Guo, Xin (Frontiers in Endocrinology, 2023)
Nonalcoholic steatohepatitis (NASH), also known as metabolic steatohepatitis, is a clinical syndrome with pathological changes like alcoholic hepatitis but without a history of excessive alcohol consumption. NASH is closely related to metabolic disorders such as obesity, insulin resistance, type 2 diabetes mellitus, and hyperlipidemia. Its main characteristics are hepatocyte steatosis with hepatocyte injury and inflammation. In severe cases, it can develop into liver cirrhosis. At present, there is no special treatment for NASH. Theabrownin (TB) is the main pigment substance in fermented tea. Theabrownin has beneficial effects on lipid metabolism and intestinal flora. However, the effect of theabrownin on NASH has not been studied. This study was aimed at exploring the effects of theabrownin from Fuzhuan brick tea on NASH. Methionine/choline deficient (MCD) diet induced NASH mice were treated with theabrownin for 4 weeks. We found that theabrownin treatment could not improve liver mass loss and steatosis. However, theabrownin ameliorated liver injury and decreased liver inflammatory response. Theabrownin also alleviated liver oxidative stress and fibrosis. Furthermore, our results showed that theabrownin increased hepatic level of fibroblast growth factor 21 (FGF21) and reduced the phosphorylation of mitogen-activated protein kinase p38 in MCD diet-fed mice.